The paleface [videorecording (DVD)] - McLeod, Norman Z., 1898-1964; Hope, Bob, 1903-2003; Russell, Jane, 1921-2011; Armstrong, Robert, 1890-1973 (Bob Hope, the tribute collection., 2002)
A timid frontier dentist finds himself gunslinging alongside the fearless Calamity Jane as she fights off outlaws and Indians.